Exposure of prepubertal beef bulls to cycling females affects neither age at puberty nor ability to pass an initial breeding soundness examination - N. Miller; Ryan M. Breiner; Tom Taul; Sharon K. Tucker; Karol E. Fike (Kansas Agricultural Experiment Station Research Reports, 2013)
Age at puberty is a crucial factor influencing a young bull's ability to pass a breeding soundness examination (BSE) at a year of age, and reducing that age may prove beneficial to beef producers. For beef females, exposure to mature bulls is known to hasten the onset of puberty and also can reduce the duration of postpartum anestrus. Relatively little research has evaluated the effects of female exposure on beef bull sexual development. Bulls are thought to use visualization rather than olfaction as their primary and preferred way to detect estrus in females. The purpose of this study was to determine whether continuous, long-term fence-line exposure of prepubertal beef bulls to estrouscycling beef females influences a bull's age at puberty and subsequent ability to pass a BSE.
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-162-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1083; Cattle; Breeding soundness examination (BSE); Estrous cycle; Puberty; Female exposure